Synthesis of g-C3N4/Nb2O5 heterostructures: study of photocatalytic properties - Silva, Gelson Tiago dos Santos Tavares da (2019)
Semiconductors are promising catalysts for artificial photosynthesis, but to date, there is no consensus on the ideal photocatalyst for CO2 reduction. Among semiconductors used for CO2 reduction, Nb2O5 is a promising alternative, since it has characteristics useful for catalysis, such as surface groups capable of assisting catalytic processes and high chemical stability. However, Nb2O5 absorbs only UV radiation, thus large-scale application of the same under solar radiation is inefficient. Given this problem, the formation of heterojunctions between Nb2O5 and C3N4, a semiconductor that absorbs below 460 nm of the visible spectrum, was investigated in this thesis as an alternative method to improve the photocatalytic properties of Nb2O5. Initially, the ability of Nb2O5 to convert CO2 in C1 and C2 products under irradiation was studied since Nb2O5 is known for its high surface acidity, a factor that could decrease the interaction of CO2 with the surface of the catalyst. However, it was observed that the surface acidity of Nb2O5 favored the formation of CO due to the low interaction of this molecule with the surface of the catalyst. This finding showed that Nb2O5 is a possible catalyst for CO2 photoreduction reactions. Accordingly, the main characteristics of Nb2O5 was verified and alternative synthesis methods for the formation of heterojunctions between Nb2O5 and g-C3N4 were investigated in order to shift the absorption of Nb2O5 into the visible region and increase its photocatalytic performance. To that end, heteroaggregation induced by difference in superficial charge was chosen. The method proved efficient for the formation of g-C3N4/Nb2O5 heterostructures, where the Nb2O5 particles were homogeneously dispersed on the surface of g-C3N4, thus conferring an intimate contact between the particles, high sharing of photogenerated charges, and consequently high photocatalytic activity for the degradation of organic pollutants and conversion of CO2 into CH4.